The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.54371/jiip.v5i1.425
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kepuasan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT. Indonesia Applicad

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh secara parsial dan simultan  kepuasan kerja dan disiplin kerja terhadap kinerja karyawan pada PT Indonesia Applicad. Metode penelitian yang digunakan adalah kuantitatif pendekatan assosiatif dengan sampel jenuh sebanyak 55 karyawan, analisis data menggunakan uji validitas, uji reliabilitas, uji asumsi klasik, analisis regresi, analisis koefisien korelasi, analisis koefisien determinasi dan uji hipotesis. Hasil penelitian menunjukkan bahwa kepuasan kerja (X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…When employee needs are met, job satisfaction is achieved. The findings in this study are different from the research of (Rosmaini & Tanjung, 2019), (Sabuhari et al, 2020), (Harahap & Tirtayasa, 2020), (Fajri et al, 2022), showing that employee satisfaction at work can have a positive impact on their performance.…”
Section: Figure 2 T-value Path Chartcontrasting
confidence: 99%
See 1 more Smart Citation
“…When employee needs are met, job satisfaction is achieved. The findings in this study are different from the research of (Rosmaini & Tanjung, 2019), (Sabuhari et al, 2020), (Harahap & Tirtayasa, 2020), (Fajri et al, 2022), showing that employee satisfaction at work can have a positive impact on their performance.…”
Section: Figure 2 T-value Path Chartcontrasting
confidence: 99%
“…The success of banking depends on employee job satisfaction; if employees are happy with their work, they will dedicate themselves to it. Based on the results of hypothesis testing by (Rosmaini & Tanjung, 2019), (Sabuhari et al, 2020), (Dewi & Frianto, 2020), (Harahap & Tirtayasa, 2020), (Fajri, Amelya, & Suworo, 2022), showed that job satisfaction improves employee performance.…”
Section: Introductionmentioning
confidence: 99%
“…The survey of respondents is conducted online using the google form facility distributed via applications Whatsapp, Telegram and Instagram so that the technique used to take samples in this research is purposive sampling technique because it is in accordance with certain considerations based on the objectives of this research. Fajri et al (2022) explain that the sample is part of the number and characteristics possessed by the population. This research in sampling uses non-probability sampling techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Jumlah pegawai faktor tersebut, merupakan atribut yang melekat dalam sebuah pelaksanaan tugas. Di lain pihak, disiplin merupakan atribut organisasi yang dihadirkan sebagai pedoman atau kendali atas perilaku kerja yang terukur (Fajri, et al, 2022). Sedangkan kepuasan merupakan atribut diri pegawai yang timbul atas respons faktor eksternal dalam pelaksanaan tugas.…”
Section: Bulanunclassified